Factorial Design in the Optimization of Preconcentration Procedure for Aluminum Determination by AAS - Dinc, Sule; Bozdogan, Abduerrezzak; Alpdogan, Guezin; Asci, Buerge; Sungur, Sidika (SPRINGER, 2009)
A preconcentration method using Amberlite XAD-16 column for the enrichment of aluminum was proposed. The optimization process was carried out using fractional factorial design. The factors involved were: pH!, resin amount, reagent/metal mole ratio, elution volume and sampling flow rate. The absorbance was used as analytical response. Using the optimised experimental conditions, the proposed procedure allowed determination of aluminum with a detection limit (3 sigma/s) of 6.1 mu g L(-1) and a quantification limit (10 sigma/s) of 20.2 mu g L(-1), and a precision which was calculated as relative standard deviation (RSD) of 2.4% for aluminum concentration of 30 pg L(-1). The preconcentration factor of 100 was obtained. These results demonstrated that this procedure could be applied for separation and preconcentration of aluminum in the presence of several matrix. In this work, a procedure for the preconcentration and determination of aluminum was proposed. The experimental conditions of the procedure were obtained by using two level fractional factorial design.
Keywords: Fractional factorial design; aluminum; morin; preconcentration; XAD-16; AAS; Biochemistry & Molecular Biology; Chemistry